2008
DOI: 10.1002/elps.200700943
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic system for the studies of single DNA molecules

Abstract: Here, we describe a simple and low-cost lithographic technique to fabricate size-controllable nanopillar arrays inside the microfluidic channels for the studies of single DNA molecules. In this approach, nanosphere lithography has been employed to grow a single layer of well-ordered close-packed colloidal crystals inside the microfluidic channels. The size of the polymeric colloidal nanoparticles could be trimmed by oxygen plasma treatment. These size-trimmed colloidal nanoparticles were then used as the etchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Nanosphere lithography was previously employed to fabricate size-tunable silicon nanopillars in a microfluidic system by Kuo et al [19]. In this experiment, the diameter of nanopillar templates could be tuned by reducing the size of polystyrene beads using cycles of oxygen plasma treatment.…”
Section: Su-8 Nanopillar Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosphere lithography was previously employed to fabricate size-tunable silicon nanopillars in a microfluidic system by Kuo et al [19]. In this experiment, the diameter of nanopillar templates could be tuned by reducing the size of polystyrene beads using cycles of oxygen plasma treatment.…”
Section: Su-8 Nanopillar Arraysmentioning
confidence: 99%
“…Polymeric nanopillars can be obtained after curing and mold release. In a previous publication [19], we demonstrated that silicon nanopillar arrays with various diameters can be fabricated inside microfluidic channels, and to fabricate polymeric nanopillar arrays for cell traction force sensing, we modified this fabrication process in the current study. Figure 1 presents a schematic view of the fabrication process.…”
Section: Introductionmentioning
confidence: 96%
“…The sizecontrollable nanopillar arrays inside the microfluidic channels were fabricated by nanosphere lithography. The gap distance between nanopillar could be tuned between 20 and 80 nm allowing the formation of nanofluidic system for single DNA molecule investigation [82]. As narrow as 20 nm channels were created by the Craighead group using the size-reduced electrospun nanofiber method [83].…”
Section: Smd In Nanofluidic Devicesmentioning
confidence: 99%
“…Moreover, a DNA molecule colliding with such a post would be minimally deformed by the channel floor and ceiling that confine the post. While there are experimental data on DNA separations in dense arrays of sub-micron diameter posts [11][12][13][14][15] and DNA collisions with isolated micron-diameter posts [16][17][18], even the most fundamental theoretical predictions [5] about the universal behavior of DNA collisions with a point-sized post remain untested.…”
Section: Introductionmentioning
confidence: 97%